Mediated Bodily Routines as Infrastructure in the Algorhythmic City - Seija Ridell (Media Theory)
This article proceeds from the observation that, in 21st century cities, algorithmic technologies engage people as bodily beings in the production of space in ways that warrant theoretical discussion on urban infrastructure and infrastructural power. While human corporeality is an increasingly prominent issue in critical (media) infrastructure studies, my argument in the article is that the structural role of corporeality in the pervasively computed urban context remains undertheorised. A key starting point demanding reconsideration concerns the ontological separation of human embodiment from the materiality of infrastructure. To overcome this separation, I direct attention to urbanites’ mediated bodily habits and routines, stressing their importance in infrastructural constitution. The power-infused interrelational dynamic that these routines enact is addressed in the article by developing a conceptualisation that combines views of classic social and urban thinkers with more recent, particularly nonrepresentational, theorisation. As a methodological bridge towards empirically investigating how mediated bodily routines ‘infrastructure’, I propose a reworking of Henri Lefebvre’s notion of rhythm in terms of the algorithmic qualities of contemporary cities.